INCREASING THE ROLE OF INTELLECTUALIZATION AND INNOVATIZATION OF JOB AND MANAGEMENT ACTIVITIES IN THE CONDITIONS OF THE NEW INDUSTRIAL REVOLUTION - Galyuk , I. B. (The actual problems of regional economy development, 2018)
The article is aimed at studying the interconnection of the possibilities of implementing the industrial revolution in Ukraine with the existing level of intellectualization and innovation activity in order to analyze the prerequisites for ensuring breakthrough performance. On the basis of the analysis of statistical data on scientific and innovation activities, it is determined that to date, the basic preconditions for the implementation of the industrial revolution are not provided. These issues can be solved only on the basis of the analysis of the triad “intellectualization - innovation - industrial revolution” as a mutually determining component of breakthrough performance.